Analysis of coaching behaviour - Franks, I. M.; Hodges, N.; More, K. (International Journal of Performance Analysis in Sport, 2001)
Effective instruction is crucial to the pursuit of optimal sporting performance. The more effective the instruction, the more fully the instructor's role will benefit athlete performance. Such instruction requires the application of skills that range from the planning, organization and presentation of learning experiences, to the provision of appropriate feedback information. Previous research (More and Franks, 1996, Journal of Sport Science, 14, 523-543) attempted to analyze the verbal coaching behaviours of coaches during a coaching practice. However, analyzing coaching behaviour with the intent of improving their instructional effectiveness assumes the existence of a "best practice" template for coaches. This paper will review recent empirical literature pertaining to this template of effective instruction and question existing concepts of "best practice" behaviours for coaches.